Draft genome sequence of Oenococcus oeni strain X2L (CRL1947) isolated from red wine of Northwest Argentina - Mendoza, Lucia Margarita (2015)
We report the draft genome sequence of Oenococcus oeni strain X2L, a potential starter culture of malolactic fermentation, isolated from Malbec wine of Argentina. Genes encoding for enzymes involved in the metabolism of malate, citrate, and nitrogen compounds, as well as aroma compounds, were found in this genome, showing its ability to improve the sensorial characteristics of wines.